The principles and practices of nutrition advocacy: evidence, experience and the way forward for stunting reduction. Issue 3 (18th September 2013) - Pelletier, David; Haider, Rukhsana; Hajeebhoy, Nemat; Mangasaryan, Nune; Mwadime, Robert; Sarkar, Satyajit
Abstract: Advocacy represents an intervention into complex, dynamic and highly contextual socio‐political systems, in which strategies and tactics must be adjusted on a continual basis in light of rapidly changing conditions, reactions from actors and feedback. For this reason, the practice of advocacy is often considered more art than science. However, capacities and practices for advocacy can be strengthened by sharing and analysing experiences in varying contexts, deriving general principles and learning to adapt these principles to new contexts. Nutrition is a particular context for advocacy, but to date, there has been little systematic analysis of experiences. The purpose of this paper is to illustrate and draw lessons from the practice of nutrition advocacy, especially in relation to stunting and complementary feeding, and suggest ways to strengthen capacities and practices in the future. The strategies and tactics, achievements and lessons learnt are described for three case studies: Uganda, Vietnam and Bangladesh. These cases, and experience from elsewhere, demonstrate that concerted, well‐planned and well‐implemented advocacy can bring significant achievements, even in short period of time. In light of the global and national attention being given to stunting reduction through the SUN (Scaling Up Nutrition) movement and other initiatives, there is now a need for much stronger investments in strategic and operational capacities for advocacy, including the human, organisational and financial resources for the advocacy and strategic communication themselves, as well as for monitoring and evaluation, supportive research and institutional capacity‐building.